The manly masquerade : masculinity, paternity, and castration in the Italian Renaissance - Finucci, Valeria (e-Duke books scholarly collection., 2003)
Analyzes how the body was constructed and politicized in early modern Italy by exploring literary discourses of the period - plays, novellas, travel journals, poems, etc.